Total synthesis of beshanzuenone D and its epimers and abiespiroside A - Borade, Balasaheb R.; Dixit, Ruchi; Kontham, Ravindar (Organic Letters, 2020)
A unified and protecting-group-free six-step total synthesis of bisabolane-type sesquiterpenoid beshanzuenone D and its stereoisomers and abiespiroside A using S-(+)-carvone as a common chiral-pool building block is disclosed. This synthetic route features chemoselective allylic chlorination of carvone, Au(I)-catalyzed cydoisomerization induced construction of furan from homopropargylic diol, substrate-controlled selective hydroxylation using Davis-oxaziridine, and dye-sensitized photo-oxidation (through O-1(2)) of hydroxyalkyl tethered furan to access oxaspirolactone as key transformations. A comprehensive set of NMR data along with DFT calculations, ECD spectra, and optical rotation measurements of the synthesized beshanzuenone D and its epimers were obtained to confirm absolute configurations.

Tris-heteroleptic ruthenium(II) polypyridyl complexes: Synthesis, structural characterization, photophysical, electrochemistry and biological properties - Bhat, Satish S.; Kumbhar, Avinash S.; Purandare, Neeraja; Khan, Ayesha; Grampp, Gunter; Loennecke, Peter; Hey-Hawkins, Evamarie; Dixit, Ruchi; Vanka, Kumar (Journal of Inorganic Biochemistry, 2020)
{Three water-soluble tris-heteroleptic ruthenium(II) polypyridyl complexes [Ru(bpy)(phen)(bpg)](2+) (1), [Ru (bpy)(dppz)(bpg)]2+ (2), and [Ru(phen)(dppz)(bpg)]2+ (3) (where bpy = 2,2'-bipyridine
Keywords: Circular dichroism; Cytotoxicity; fluorescence; Polypyridyl; ruthenium